Pengaruh Perceived Organizational Support terhadap Work Engagement pada Karyawan Hospitality Industry - Deska Suci Avianti; Muhammad Ilmi Hatta (Bandung Conference Series: Psychology Science, 2022)
Abstract. Organizations need employees who are bound to their work so they will give maximum effort in doing work (Jin & McDonald, 2017). Employees who are bound to their work are known as work engagement. Work engagement is a positive and satisfying state of mind that related to work which is characterized by vigor, dedication, and absorption (Schaufeli et al., 2002). Work engagement will be present when job demands and job resources are high. One of the job resources is perceived organizational support which consists of three dimensions, namely fairness, supervisor support, andorganizational rewards and job conditions. This study aims to see how much influence perceived organizational support and its dimensions have on work engagement in 130 employees of the hospitality industry. The measuring instrument that used is UWES-17 (Utrecht Work Engagement Scale-17) which refers to the theory of Schaufeli et al. (2002) and SPOS (Survey Perceived Organizational Support) which refers to the theory of Eisenberger et al. (1986). The sampling technique that used is purposive sampling. The method that used is a quantitative method of causality with multiple linear regression analysis techniques. The results show that perceived organizational support has a significant effect on work engagement by 0.495 or 49.5%. The fairness dimension has an effect of 22.9%, the supervisor support dimension has an influence of 19.2%, and the dimensions of organizational rewards and job conditions have an influence of 7.4%. Abstrak. Organisasi membutuhkan karyawan yang terikat dengan pekerjaannya sehingga akan memberikan usaha yang maksimal dalam melakukan pekerjaan (Jin & McDonald, 2017). Karyawan yang terikat dengan pekerjaannya dikenal dengan istilah work engagement. Work engagement adalah keadaan pikiran yang positif dan memuaskan yang terkait dengan pekerjaan yang dicirikan dengan vigor, dedication, dan absorption (Schaufeli et al., 2002). Work engagement akan hadir ketika job demands dan job resources tinggi. Salah satu job resources adalah perceived organizational support yang terdiri dari tiga dimensi, yaitu fairness, supervisor support, serta organizational rewards dan job conditions. Penelitian ini bertujuan untuk melihat seberapa besar pengaruh perceived organizational support dan dimensi-dimensinya terhadap work engagement pada 130 karyawan hospitality industry. Alat ukur yang digunakan adalah UWES-17 (Utrecht Work Engagement Scale-17) yang mengacu pada teori Schaufeli et al. (2002) dan SPOS (Survey Perceived Organizational Support) yang mengacu pada teori Eisenberger et al. (1986). Teknik sampling yang digunakan adalah purposive sampling. Metode yang digunakan adalah metode kuantitatif kausalitas dengan teknik analisis regresi linier berganda. Hasilnya menunjukkan bahwa perceived organizational support berpengaruh secara signifikan terhadap work engagement sebesar 0.495 atau 49.5%. Dimensi fairness memiliki pengaruh sebesar 22.9%, dimensi supervisor support memiliki pengaruh sebesar 19.2%, serta dimensi organizational rewards dan job conditions memiliki pengaruh sebesar 7.4%.